2016
DOI: 10.1007/s00394-016-1164-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urinary Na/K ratio among Lebanese elementary school children is attributable to low K intake

Abstract: About 50 % of children exceeded the recommended daily upper intake for Na, while the majority was below K adequate intake. This unfavorable Na/K ratio is indicative of potentially negative health effects at later stages in life. Interventions aimed at reducing salt intake and increasing consumption of fruits and vegetables are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A similar finding was also described in studies on Indonesian older women that Na intake from the dietary method was less than that in urine; on the other hand, K intake from the dietary method was greater than that in urine [27]. Another paucity of this study is that we applied spot urines rather than 24 h urinary excretion, although these methods have been validated and performed by a previous study [21].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…A similar finding was also described in studies on Indonesian older women that Na intake from the dietary method was less than that in urine; on the other hand, K intake from the dietary method was greater than that in urine [27]. Another paucity of this study is that we applied spot urines rather than 24 h urinary excretion, although these methods have been validated and performed by a previous study [21].…”
Section: Discussionmentioning
confidence: 52%
“…Other authors have reported higher K intakes than those in our study. A potassium intake of 46.6 ± 23.02 mg/d was reported in Lebanese subjects [21], Grimes et al [31] in the SONIC study recorded 54 ± 2 mg/dl, and Oliveira et al [40] reported an average of 43 mmol/d on 8% of children who met the WHO recommendation for K intake. However, our finding is similar to that of two previous studies demonstrating mean K intake in children was approximately 1000mg/d; Kristbjornsdottir et al [41] showed an average of 1210 mg/d (31 mmol/d) for subjects aged 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation